Islamism, and the ideological questioning of the pancasila - Mahfuh Haji Halimi (2018)
This study investigates the existential threat that non-integrative and pro-jihad Islamists and their organisations pose to the Negara Kesatuan Republik Indonesia (NKRI, Unitary State of the Republic of Indonesia). The three case studies chosen for analysis of their origin and development, ideology and strategy are Al-Jama‘ah Al-Islamiyyah (JI), Majelis Mujahidin Indonesia (MMI) and Jama’ah Ansharut Tauhid (JAT). After determining the existential threat, the study then proceeds to understand the post-Suharto government’s weak response to them. What could be the reasons for the state’s indecisiveness to securitise them? Why is it difficult for the state to convince the Indonesian population in general, and more specifically, religious leaders in Nahdlatul Ulama (NU) and Muhammadiyah as well as public intellectuals that these Islamists are an existential threat to the unitary Pancasila state? This study argues that the absence of a consensus between the securitisers and the relevant audience, the Indonesian population, on the existential threat posed by them is the reason for the post-Suharto Indonesian state finding it difficult to securitise them. To obtain first-hand information, I conducted interviews, talked, and discussed with people from among the securitisers and relevant audience. By employing qualitative analysis of the primary and related documents, this study evaluates the intentions and capabilities of the chosen case studies. After that, an assessment was also made on the post-Suharto government’s securitisation of them. This study concludes that non-integrative and pro-jihad Islamists are an existential threat to the NKRI. To securitise them the government must secure the mandate of the general Indonesian public by allocating more resources to convince them and develop a consensus on the existential threat posed by the non-integrative and pro-jihad Islamists. Since Indonesia is becoming a stronger “negara hukum” (a state that implements its government based on the rule of law) because of the establishment of democracy, the government must find the right balance of actions to act against the non-integrative and pro-jihad Islamists. A preventive law like the Internal Security Act of Singapore or the Security Offences (Special Measures) Act 2012 (SOSMA) which Malaysia is currently implementing might not be the solution in the short term. Implementation of such measures would only be possible if the government is successful in convincing the general Indonesian population as the relevant audience of the existential threat. In this regard, the politically aware public and the leadership of the largest Muslim organisations (NU and Muhammadiyah) must agree that non-integrative and pro-jihad Islamists and their organisations are indeed an existential threat. They must allow the government to formulate and implement policies necessary to contain the threat.